Enhancing the explosive characteristics of a Semtex explosive by involving admixtures of BCHMX and HMX - Elbeih, Ahmed Ikhlas Mohamed; Hussein, Ahmed Khaled Mohamed; Elshenawy, Tamer; Zeman, Svatopluk; Hammad, Sara; Baraka, Ahmad; Elsayed, Mohamed; Gobara, Mohamed; Tantawy, Hesham (My University, 2020)
A well-known ternary plastic explosive, Czech Semtex 1H, contains a mixture of PETN and RDX softened by SBR. In this work, BCHMX was used to replace PETN in Semtex 1H to form Sem-BCþRDX. In addition, another mixture based on BCHMX and HMX as energetic fillers bonded by the polymeric matrix of Semtex 1H (Sem-BCþHMX) was studied. The particle size distribution of each individual explosive was determined to obtain the optimum mixing conditions. Friction and impact sensitivities were determined. The velocity of detonation was reported practically and the detonation properties were calculated by EXPLO5 code. The explosive strength of each sample was measured by the ballistic mortar test. The conclusion confirms that the velocity of detonation of Sem-BCþHMX was the highest in comparison with the prepared samples. Sem-BCþRDX has the least impact and frictions sensitivities. Sem-BCþRDX has higher detonation velocity, detonation properties and explosive strength than Semtex 1H. Addition of BCHMX in Semtex 1H as a replacement for PETN is the candidate to produce a high performance advanced Czech plastic explosive.
Zvýšení výbušných charakteristik trhaviny Semtex zahrnutím příměsí BCHMX a HMX
Keywords: semtex; explosives; combustion; sensitivity; detonation; explosive strength; semtex; výbušiny; spalování; citlivost; detonace; výbušná síla